2019
DOI: 10.3390/nu11081857
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water Homeostasis in Muscle Function and Frailty: A Review

Abstract: Water, the main component of the body, is distributed in the extracellular and intracellular compartments. Water exchange between these compartments is mainly governed by osmotic pressure. Extracellular water osmolarity must remain within very narrow limits to be compatible with life. Older adults lose the thirst sensation and the ability to concentrate urine, and this favours increased extracellular osmolarity (hyperosmotic stress). This situation, in turn, leads to cell dehydration, which has severe conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 106 publications
(136 reference statements)
2
105
0
3
Order By: Relevance
“…Altered expressions or functions of AQPs lead to fluid loss, and this loss is closely associated with cell aging 15 . Furthermore, AQPs can also facilitate the diffusion of reactive oxygen species, which lead to cellular alterations related to cell aging 15,27 . Studies have showed that functional AQP1 is inserted into the plasma membrane 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Altered expressions or functions of AQPs lead to fluid loss, and this loss is closely associated with cell aging 15 . Furthermore, AQPs can also facilitate the diffusion of reactive oxygen species, which lead to cellular alterations related to cell aging 15,27 . Studies have showed that functional AQP1 is inserted into the plasma membrane 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The fluid exchange between extramuscular and intramuscular compartments is a complex interplay between hydrostatic and osmotic forces, governed by anatomical and biochemical factors (Lorenzo et al, 2019; Senay & Pivarnik, 1985; Sjogaard & Saltin, 1982). In line with previous literature, we found a rapid initial increase of ACSA with the onset of exercise after 2.5 min of running.…”
Section: Discussionmentioning
confidence: 99%
“…Water is an essential component of the human body with important metabolic, transport, temperature control, structural, and mechanical functions (Lorenzo, Serra‐Prat, & Yébenes, 2019). In skeletal muscle, for example, fluid flows are crucial in the regulation of ion concentrations and pH, which affect muscle contraction and hence force development during exercise (Sjogaard & Saltin, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the intake of additional amounts of protein of as little as around 5 g/day, resulted in an unadjusted average increase in lean body mass of about 500 g, and on adjusting for confounding factors, an average increase in lean body mass of about 1200 g was seen. Water accounts for about 76% of muscle, 20 and considering that 80% of the dry weight is made up of protein, the amount of muscle protein assimilated during the intervention period is estimated to be approximately 240 g (multivariate-adjusted model results). Since in those studies with protein interventions of < 10 g/day energy balance was not negative in all subjects, if 5 g/day of supplementary protein was digested and absorbed at an absorption rate of 81%, 21 it takes approximately 59 days (eight weeks), assuming that all absorbed amino acids are used in increasing lean body mass.…”
Section: Effects With Low Dosesmentioning
confidence: 99%